2012
DOI: 10.2341/10-130-l
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Dehydration Periods of Crown Fragments Prior to Reattachment

Abstract: Compared to a 30-minute period, a 24-hour rehydration of the tooth fragment before treatment seems to salvage enough moisture to result in an increase in reattachment strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 23 publications
4
44
1
Order By: Relevance
“…In relation to the dental fragment rehydration process, the Capp et al study showed that BS could be recovered in a tooth whose fragment was dehydrated for a period of 48 hour, if the fragment was rehydrated with distilled water for 30 min prior to reattachment, resulting in a BS value equivalent to 167.59 N. The same study showed that the value of the BS was higher if the fragment was kept hydrated, attaining 184.36 N . Shirani et al showed that teeth rehydrated with distilled water for a period of 24 hours presented higher BS values than those rehydrated for 30 minute prior to the reattachment. However, when the fragment was dehydrated for a period of 30 minute or less, rehydration with distilled water 30 min before reattachment can promote recovery of part of the BS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the dental fragment rehydration process, the Capp et al study showed that BS could be recovered in a tooth whose fragment was dehydrated for a period of 48 hour, if the fragment was rehydrated with distilled water for 30 min prior to reattachment, resulting in a BS value equivalent to 167.59 N. The same study showed that the value of the BS was higher if the fragment was kept hydrated, attaining 184.36 N . Shirani et al showed that teeth rehydrated with distilled water for a period of 24 hours presented higher BS values than those rehydrated for 30 minute prior to the reattachment. However, when the fragment was dehydrated for a period of 30 minute or less, rehydration with distilled water 30 min before reattachment can promote recovery of part of the BS .…”
Section: Resultsmentioning
confidence: 99%
“…Shirani et al showed that teeth rehydrated with distilled water for a period of 24 hours presented higher BS values than those rehydrated for 30 minute prior to the reattachment. However, when the fragment was dehydrated for a period of 30 minute or less, rehydration with distilled water 30 min before reattachment can promote recovery of part of the BS . Using the same rehydration time (24 hour) for all groups analyzed, the Shirani et al study showed that teeth with the highest BS values were those that used milk (374.20 N) or saliva (328.6 N) as a moisturizing solution for the dental fragment, whereas a later Sharmin et al study showed that the group presenting the highest BS values was rehydrated in saline for a period of 24 h (75.91 N).…”
Section: Resultsmentioning
confidence: 99%
“…Transport the fragment in an appropriate solution: Hank's Balanced Solution (HBSS), milk, egg white, hypertonic dextrose solution or saliva, water [4][5][6][7][8]. If these solutions are not available, store the fragment in the patient's saliva [17].…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the tooth fragment has been recovered and stored in a recommended solution, reattachment of the fragment is possibly. Tested and recommended solutions are: Hank's Balanced Solution (HBSS), milk, egg white, hypertonic dextrose solution or saliva, water [4][5][6][7][8]. However, other treatments could be considered: class IV direct composite restoration, direct composite veneer, indirect ceramic veneer, post and cores, and indirect full prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a key step in the treatment of fractured teeth and should be routinely conducted to avoid any flaws in the restoration of teeth that could compromise the bonding and esthetics; the fragment cannot regain its original color when it is dehydrated. 17 The limitations can be controlled by strictly following the adhesive protocol in order to ensure good fracture resistance and to maintain a satisfactory esthetic appearance without compromising the remaining dental tissue. 15 …”
Section: Advantages and Disadvantagesmentioning
confidence: 99%